The perceived motivations behind the introduction of the law on external audit in Vietnam. Issue 1 (3rd January 2017) - Nguyen, Phuong Thi; Kend, Michael
Abstract : Purpose: Over the past 20 years, external auditing activities and practices in Vietnam have developed quickly. An important milestone is the first Law on External Audit No. 67/2011/QH12 which has been passed by the National Assembly of Vietnam on 29 March 2011. The purpose of this paper is to understand the perceived motivations in regard to the introduction of the Law on External Audit, through the eyes of various key stakeholders. There has been genuine public interest concerns regarding audit quality in Vietnam as prior academic research has indicated, and this is the first study to examine whether the new audit reforms where introduced specifically to deal with those concerns. Design/methodology/approach: Face-to-face semi-structured interviews were conducted with 45 key stakeholders during 2014 in both Ha Noi and Ho Chi Minh City, Vietnam. Findings: The study finds that the Law on External Audit was introduced because it holds the highest form of regulatory authority in Vietnam, and the lower level Decrees that existed before the law did not even detail the audit firms' responsibilities resulting in low audit quality. Also, the new Law was introduced to add more credibility and trust in the external audit function in Vietnam, and to reduce unfair price competition. However, some of our findings indicate that the Governments' motivations were not all purely public interest related. A theoretical framework is developed to evaluate whether these reforms are substantive enough in nature to effect public confidence in reported financial data and audits. Originality/value: External auditing plays a crucial role in any market-based economy. In a developing economy, audit quality is often perceived to be lower than in a developed economy. Therefore, it is not uncommon to observe governments in developing economies producing tighter regulations for the auditing and assurance market to help attract more foreign investment and to establish credibility and more trust. In Vietnamese context, the current study conveys that the new audit reforms not only were introduced with genuine public interest concerns but also were a mechanism to protect the government's interests.